CT Imaging Findings of Pulmonary Artery Stenosis: A Pictorial Review - Zhang, Mengdi; Chen, Li; Bu, Chao; Zhang, Hanxi; Luo, Jing; Wang, Jing; Sun, Qihua; Liu, Qingyu; Sun, Zhonghua; Li, Yu (MDPI AG, 2024)
Pulmonary artery stenosis represents a group of disorders involving main, branch or peripheral pulmonary arteries with pain, dyspnea, hemoptysis or even no symptoms. Early diagnosis and timely intervention are crucial for reducing mortality, but timely diagnosis is challenging due to the non-specific symptoms. Computed tomography pulmonary angiography (CTPA) is useful in the diagnosis because it can provide more details about abnormal changes in the lumen, vessel wall and adjacent mediastinal structures. Congenital and acquired pulmonary artery anomalies have some characteristics on CTPA, which can be useful for differential diagnosis. Awareness of these conditions is important for radiologists. This pictorial review provides an overview of CTPA imaging features of pulmonary artery stenosis.